2018
DOI: 10.1111/nicc.12349
|View full text |Cite|
|
Sign up to set email alerts
|

Lived experiences of intensive care nurses in caring for critically ill patients

Abstract: Intensive care nurses need to enhance their knowledge and skills related to the use of technologies and patient care by attending training programs and gaining further education. This study recommends that hospital administrators should support sufficient facilities and technologies of care and, in particular, increase the competency of nurses in caring for critically ill patients as the whole person.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…[ 41 ] Research has shown that nurses were better cared for in critical situations because of their professional duties, sense of responsibility to society, religious beliefs, and thinking of the patient as a member of their own family. [ 3 42 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 41 ] Research has shown that nurses were better cared for in critical situations because of their professional duties, sense of responsibility to society, religious beliefs, and thinking of the patient as a member of their own family. [ 3 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare systems faced a dramatic increase in cases of COVID-19, and the shortage of hospital beds, ventilators, and general equipment on the one hand, and the increasing need for healthcare workers on the other, became a major challenge. [ 3 ] Nurses have always been at the frontline of combat and control specific epidemics such as SARS, MERS, and influenza. The main responsibility of nurses in legal and moral terms is to take care of clients in clinical settings and in the community, and it is expected that they will provide good quality care to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena are not particular to the UK as illustrated to varying degrees by papers of Limbu et al . () and Jarden et al . () below.…”
mentioning
confidence: 88%
“…To this end, Limbu et al . () undertook a phenomenological inquiry to investigate the lived experience of 13 Nepalese nurses from three ICUs. Seven categories emerged from data analysis, which related to the lifeworlds of space, time, relations and body: low technology of care and insufficient resources (lived space); physical and psychological distress and requiring competency (lived body); connecting relationships of a family, trusting technology and realizing team working (lived relationships); less time to be with patient as a whole person (lived time).…”
mentioning
confidence: 99%
“…Caring for critically ill persons is often associated with emotional and physical exhaustion (10)(11)(12)(13). The sudden occurrence of the COVID-19 pandemic, which healthcare systems were seemingly unprepared for alongside increasing mortality rates in some areas have contributed to the development of fear, worry and uncertainty (14).…”
Section: Introductionmentioning
confidence: 99%